1989
DOI: 10.1002/aoc.590030311
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on acute toxicity of methylarsonic acid, dimethylarsinic acid and trimethylarsine oxide in mice

Abstract: The acute toxicity of methylarsonic acid, CH3AsO(OH)2 (MAA), dimethylarsininc acid, (CH3)2AsO(OH) (DMAA), and trimethylarsine oxide, (CH3)3As0 (TMAO), were examined in mice with oral administration.The LDS0 values of MAA, DMAA and TMAO were 1.8, 1.2 and 10.6 g kg-' respectively. The toxicity of MAA and DMAA was very much lower than that for inorganic arsenic compounds. It was shown that TMAO has a similar acute toxicity to arsenobetaine. On the other hand, when the mice were administered 14.4 g kg-' of TMAO on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…The oral LD50s of MMA(V) and its sodium salts are 1.8 g/ kg in mice (Kaise et al, 1989) and >800 mg/kg (Gaines and Linder, 1986) in rats. The reproductive capacity of male mice repeatedly administered the monosodium salt of MMA(V) (MSMA) (11.9 and 119 mg/kg) over several weeks was reduced (Prukop and Savage, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The oral LD50s of MMA(V) and its sodium salts are 1.8 g/ kg in mice (Kaise et al, 1989) and >800 mg/kg (Gaines and Linder, 1986) in rats. The reproductive capacity of male mice repeatedly administered the monosodium salt of MMA(V) (MSMA) (11.9 and 119 mg/kg) over several weeks was reduced (Prukop and Savage, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of inorganic arsenic to form both DMA and methylarsonic acid (MMA) has traditionally been viewed as a mechanism to facilitate the detoxification and excretion of arsenic. This is principally because DMA, in particular, is over 10-fold less acutely toxic than inorganic arsenic (Kaise et al, 1985(Kaise et al, , 1989. However, evidence suggesting that DMA itself has unique toxic properties has accumulated in the * Corresponding author.…”
mentioning
confidence: 99%
“…The methylation of inorganic arsenicals was initially thought to be a detoxification process because the toxicity of MMAs V and DMAs V is substantially lower than that of inorganic arsenicals. 7,8) However, it was recently reported that toxic MMAs III and DMAs III might be produced through the methylation of inorganic arsenicals, 9,10) and that arsenical-glutathione conjugates, such as MMAs III DG and DMAs III G, might be generated in vivo. [12][13][14] 1830 Vol.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) It is believed that methylation of inorganic arsenicals results in a reduction in general toxicity, as indicated by their increased in vivo lethal dose in 50% of a population (LD 50 ) and in vitro lethal concentration in 50% of a population (LC 50 ). 7,8) However, recent studies have increasingly suggested that the methylation of inorganic arsenicals is not a universal detoxification mechanism. Some researchers have reported that trivalent methyl arsenicals, such as monomethylarsonous acid (MMAs III ) and dimethylarsinous acid (DMAs III ), were found in urine collected from people who had been exposed to high concentrations of inorganic arsenicals, 9,10) and that synthetic trivalent methyl arsenicals, such as monomethylarsine oxide (MMAs III O) and iododimethylarsine (DMAs III I), are more cytotoxic in vitro than inorganic arsenicals and pentavalent methyl arsenicals.…”
mentioning
confidence: 99%